14 Years Later: A Follow-Up Case-Study Analysis of 8 Health Professions Education Scholarship Units. (April 2020) - Humphrey-Murto, Susan; O'Brien, Bridget; Irby, David M.; van der Vleuten, Cees; ten Cate, Olle; Durning, Steven; Gruppen, Larry; Hamstra, Stanley J.; Hu, Wendy; Varpio, Lara
Abstract : Purpose: Internationally, health professions education scholarship units (HPESUs) are often developed to promote engagement in educational scholarship, yet little is known about how HPESUs change over time or what factors support their longevity. In hopes of helping HPESUs thrive, this study explored factors that shaped the evolution of 8 HPESUs over the past 14 years. Method: This study involved retrospective case-study analysis of the 8 American, Canadian, and Dutch HPESUs profiled in a 2004 publication. First, the research team summarized key elements of HPESUs from the 2004 articles, then conducted semistructured interviews with the current unit directors. In the first set of questions, directors were asked to reflect on how the unit had changed over time, what successes the unit enjoyed, what enabled these successes, what challenges the unit encountered, and how these challenges were managed. In the second set of questions, questions were tailored to each unit, following up on unique elements from the original article. The team used Braun and Clarke's 6-phase approach to thematic analysis to identify, analyze, and report themes. Results: The histories of the units varied widely—some had grown by following their original mandates, some had significant mission shifts, and others had nearly disappeared. Current HPESU directors identified 3 key factors that shaped their HPESU's longitudinal development: the people working within and overseeing the HPESU (the need for a critical mass of scholars, a pipeline for developing scholars, and effective leadership), institutional structures (issues of centralization, unit priorities, and clear messaging), and funding (the need for multiple funding sources). Conclusions: Study findings offer insights that may help current HPESU directors to strategically plan for their unit's continued development. Tactically harnessing the factors identified could help directors ensure their HPESU's growth and contend with the challenges that threaten the unit's success. Abstract : Supplemental Digital Content is available in the text.